2010
DOI: 10.1001/archoto.2010.217
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy in Head and Neck Mucosal Melanoma

Abstract: this large retrospective study suggests that postoperative radiotherapy improves the locoregional control of HNMM. The higher rate of distant metastasis was due to more advanced disease in the SRT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
2
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 24 publications
5
72
2
7
Order By: Relevance
“…We did not find that postoperative radiotherapy improved survival significantly in our study. However, two major studies have found that postoperative radiotherapy improved local control for patients with positive margins, but had no effect on survival [21,22]. Other studies have not found any effect on either local control or survival [23].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find that postoperative radiotherapy improved survival significantly in our study. However, two major studies have found that postoperative radiotherapy improved local control for patients with positive margins, but had no effect on survival [21,22]. Other studies have not found any effect on either local control or survival [23].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of adjuvant irradiation improves local-regional control, but not OS. For all mucosal sites in the head and neck, 5-year survival is approximately 25 % [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Benlyazid ve ark. nın [15] çok merkezli 160 hastalık geriye dönük çalışma-sında tek başına cerrahi olan 82 hasta ve ameliyat sonrası RT alan 78 hasta değerlendirilmiştir. Bu geniş çap-lı çalışmada lokorejyonel kontrol ameliyat sonrası RT kolunda daha yüksek bulunmuştur.…”
Section: Discussionunclassified